Light intensity and N/P nutrient affect the accumulation of lipid and unsaturated fatty acids by Chlorella sp. (September 2015) - Guo, Xiaoyi; Su, Gaomin; Li, Zheng; Chang, Jingyu; Zeng, Xianhai; Sun, Yong; Lu, Yinghua; Lin, Lu
Highlights: High lipid content was obtained in control medium under high light intensity. Lipid and UFA contents were observably enhanced by higher light intensity. N/P in mediums notably affected the lipid and UFA content. Abstract: In this study, different light intensities (80, 160, 240 and 320 μmol/m 2  s) and various mediums including control medium (CM), N/P rich medium (NPM), N rich medium (NM), and P rich medium (PM) were applied for cultivation of Chlorella sp. It was revealed that cultivation of Chlorella sp. in CM under the light intensity of 320 μmol/m 2  s led to a lipid content up to 30% enhancement, which was higher than the results of other cases. A rather high unsaturated fatty acid (UFA) content of 7.5% and unsaturated fatty acid/total fatty acid (UFA/TFA) ratio of 0.73 were obtained under 320 μmol/m 2  s in CM, indicating that the CM-320 system was applicable for the generation of UFA. Moreover, Chlorella sp. cultivated in PM under 320 μmol/m 2  s provided higher TFA content (7.3%), which was appropriate for biofuel production.